Quick-freezing based on a nitrogen reversed Brayton cryocooler prototype: Effects on the physicochemical characteristics of beef longissimus thoracis muscle. (December 2022) - Biglia, A.; Messina, C.; Comba, L.; Ricauda Aimonino, D.; Gay, P.; Brugiapaglia, A.
Abstract: Freezing plays an important role in food preservation and shelf-life extension. This study assessed the effectiveness of an innovative quick-freezing plant for meat freezing, based on a nitrogen reversed Brayton cryocooler prototype able to reach very cold temperatures (< −100 °C), by evaluating the effects on the physicochemical characteristics of frozen/thawed beef steaks. A comparison with two other standard freezing methods was conducted, and unfrozen beef steaks were used as a reference. The time-temperature profiles were monitored during the freezing and thawing processes, and physicochemical analyses were performed on unfrozen and thawed steaks. The results of the experimental campaign showed that the prototype plant made it possible to achieve a faster freezing rate (50 °C h −1 ) than standard plants, leading to a significant reduction in the thawing losses of frozen meat. In addition, the steaks processed in the prototype plant had larger hue values, indicating less red colour. Industrial relevance: In the food cold chain, especially for highly perishable products such as meat, freezing plays a significant role in preservation and shelf-life extension, thus improving safe food consumption for humans. In this study, a prototype of a nitrogen reversed Brayton cryocooler was developed and tested under the realistic conditions expected for quick meat freezing. The results showed a very fast freezing rate of the food product. Our findings demonstrated that reversed Brayton cryocoolers show great promise in the food industry for quick freezing at very low temperatures, with the potential to freeze several kinds of food products. Highlights: A reversed Brayton cryocooler prototype was used to freeze meat at about −60 °C. Effects on the physicochemical characteristics of beef loins were studied. The cryocooler prototype drastically reduced the beef loins freezing time. The cryocooler prototype significantly reduced the beef loins thawing losses.